Risk Estimation of Anterior Cruciate Ligament (ACL) Injury in East Java Puslatda Pencak Silat Athletes - Farhan Nur Ahmad Dzakiya; Damayanti Tinduh; Dwikora Novembri Utomo (Surabaya Physical Medicine and Rehabilitation Journal, 2021)
Background: Dr. Soetomo General Hospital Sports Clinic Surabaya reported that the incidence of knee injuries was rather high, particularly in martial art athletes. Injuries in pencak silat athletes are dominated by Anterior Cruciate Ligament (ACL) injuries (16.7%) Several risk factors are thought to influence ones’ propensity for these injuries.Aim: To analyze risk estimation between intrinsic and extrinsic factors in the occurrence of ACL injury in East Java Puslatda Pencak Silat Athletes.Material and Methods: This study was an analytic observational study with a case control design involving 18 pencak silat athletes from East Java Regional Training Centre. Age, gender, body mass index, previous ACL injury, range of motion, laxity, and flat foot were included as intrinsic factors; while duration of each training, training frequency, and sparring frequency were included as extrinsic factors. Data analysis was done using the Chi-Square Test. Odds Ratio was calculated through cross-tabulation.Results: It was found that 3 of 18 athletes (16.7%) had ACL injuries. None of the intrinsic and extrinsic factors significantly affected the incidence of ACL injury (p> 0.05). However, the odds ratio calculation showed that adult athletes older than 25 years-old (OR = 1.4), male (OR = 1.667), obese (OR = 1.4), with laxity (OR = 2.5), and flat foot (OR = 1) had higher risk in having ACL injury.Conclusion: Adult athletes, male, obese, with laxity, and flat foot had a higher risk of ACL injury.